2019
DOI: 10.1002/csr.1753
|View full text |Cite
|
Sign up to set email alerts
|

Does board diversity affect quality of corporate social responsibility disclosure? Evidence from Pakistan

Abstract: The study proposed that the effect of board diversity on quality of corporate social responsibility (QCSR) disclosure in Pakistan should be patterned differently from existing literature of other nations. The study has focused seven different dimensions of board diversity such as age, gender, nationality, ethnicity, educational level, educational background, and tenure across 86 firms listed in Pakistan Stock Exchange from 2010 to 2017. The results of panel regression supported resource-based view theory and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 72 publications
13
129
4
Order By: Relevance
“…Wasiuzzaman and Wan Mohammad (2020) studies the impact of board gender diversity and ESG performance of Malaysian firms and reports a positive association. Khan et al (2019) also find similar results while studying the effect of gender on CSR practices of Pakistani firms. The literature on board gender diversity and ESG performance is limited.…”
Section: Observed Relationshipssupporting
confidence: 63%
“…Wasiuzzaman and Wan Mohammad (2020) studies the impact of board gender diversity and ESG performance of Malaysian firms and reports a positive association. Khan et al (2019) also find similar results while studying the effect of gender on CSR practices of Pakistani firms. The literature on board gender diversity and ESG performance is limited.…”
Section: Observed Relationshipssupporting
confidence: 63%
“…Our argument is consistent with the lines of stakeholder and institutional point of view as well as the findings of Hossain et al 2017;Mahmood et al 2018;Masud et al 2018a, b. Moreover, the most recent study of Khan et al 2019 andMahmood et al 2018 found that board diversity (women board member, age, nationality, tenure) and the CSR committee has a significant impact in the sustainability disclosure of Pakistan.…”
Section: Findings and Discussion (Continued)supporting
confidence: 91%
“…This discussion confirms that CSR disclosure is significantly growing in Pakistan. Additionally, the latest study of Khan et al 2019 documented that board diversity variables like; gender, nation, tenure and educational qualification has a significant influence on CSR disclosure of Pakistani firms.…”
Section: Corporate Sustainability Reporting In Pakistanmentioning
confidence: 99%
See 2 more Smart Citations